2006
DOI: 10.1080/14734220600962805
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and synaptic organization of GABAA receptors in the cerebellum: Effects of targeted subunit gene deletions

Abstract: GABA A receptors form heteromeric GABA-gated chloride channels assembled from a large family of subunit genes. In cerebellum, distinct GABA A receptor subtypes, differing in subunit composition, are segregated between cell types and synaptic circuits. The cerebellum therefore represents a useful system to investigate the significance of GABA A receptor heterogeneity. For instance, studies of mice carrying targeted deletion of major GABA A receptor subunit genes revealed the role of a subunit variants for recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 94 publications
4
32
0
Order By: Relevance
“…We showed intense UT labeling in Purkinje cell bodies and ramifications as well as in glial Bergmann-GFAP positive long processes where it co-localizes with γ 1 and, to a lesser extent, with γ 2 subunits of the GABA A R, and in astrocytes co-cultured with granule neurons. Together, this corroborates previous studies establishing expression of α 5 , γ 1 and γ 3 subunits in the PCL [68], [69], and of γ 1 mRNA in Bergmann glia [70], [71]. We confirmed the coexpression of GABA A R subunits with UT in native human astrocytes and in the U87 glioma cell line.…”
Section: Discussionsupporting
confidence: 92%
“…We showed intense UT labeling in Purkinje cell bodies and ramifications as well as in glial Bergmann-GFAP positive long processes where it co-localizes with γ 1 and, to a lesser extent, with γ 2 subunits of the GABA A R, and in astrocytes co-cultured with granule neurons. Together, this corroborates previous studies establishing expression of α 5 , γ 1 and γ 3 subunits in the PCL [68], [69], and of γ 1 mRNA in Bergmann glia [70], [71]. We confirmed the coexpression of GABA A R subunits with UT in native human astrocytes and in the U87 glioma cell line.…”
Section: Discussionsupporting
confidence: 92%
“…However, ablation of GABA A Rs by targeted deletion of an α subunit variant often results in the disruption of postsynaptic gephyrin clusters and formation of large intra-cellular gephyrin aggregates [56,[72][73][74][75][76], confirming the dependence of gephyrin on GABA A Rs for postsynaptic localization. Importantly, in thalamic neurons expressing both α1-GABA A R postsynaptically and α4-GABA A R extrasynaptically, gephyrin clustering was not rescued following α1 subunit deletion, indicating that α4-GABA A R cannot interact with gephyrin [75,56].…”
Section: Heterogeneity Of Gabaergic Synapses Revealed In Mice With Tamentioning
confidence: 93%
“…Early studies in GABA A R subunit knockout (KO) mice have indicated an important role for GABA A Rs in GABAergic synapse development. Genetic deletion of the α1 subunit abolished GABAergic synaptic transmission in mature cerebellar Purkinje neurons (Fritschy and Panzanelli, 2006; Patrizi et al, 2008). Interestingly, detailed analysis reveals an intricate mechanism underlying the loss of GABAergic synaptic transmission.…”
Section: Receptorsmentioning
confidence: 99%